P2Y12 inhibition by clopidogrel increases adverse clinical outcomes in patients undergoing transcatheter aortic valve replacement. (25th November 2020) - Matsushita, K; Marchandot, B; Kibler, M; Sato, C; Heger, J; Peillex, M; Trimaille, A; Hess, S; Grunebaum, L; Ohana, M; Reydel, A; Jesel, L; et al.
Abstract: Introduction: Current recommendations support short-term dual antiplatelet therapy (DAPT) for patients undergoing transcatheter aortic valve replacement (TAVR) despite no relevant study exploring the extent of platelet inhibition by clopidogrel. Purpose: To assess whether P2Y12 inhibition by clopidogrel as evaluated by vasodilator-stimulated phosphoprotein flow cytometry test (VASP-FCT) impacts 1-year clinical outcomes in patients undergoing TAVR. Methods: Patients were included in a prospective registry between February 2010 and May 2019. VASP-FCT was assessed 24h after the procedure. Responder to clopidogrel was defined by a platelet reactivity index ≤50%. Results: Of 640 patients who underwent TAVR with preprocedural clopidogrel therapy, we enrolled 491 patients for whom VASP data were available. Responders were identified in 22% (n=110) of patients and low responders were 78% (n=381) of patients. Low body mass index, active cancer, and clopidogrel on admission were found to be independent predictors of responder. Mean transaortic pressure gradient was lower in the responder group at 1-month post-TAVR (9.9±4.4 mmHg vs. 11.2±5.8 mmHg, p=0.03) but was similar at 1-year (11.5±6.2 mmHg vs. 11.9±7.4 mmHg, p=0.74). By multivariate Cox regression analysis, patients responding to clopidogrel (hazard ratio [HR]: 2.19; 95% confidence interval [CI]: 1.04 to 3.64; p=0.04), prior PCI (HR: 2.12; 95% CI: 1.07 to 4.37; p=0.03), and mean transaortic pressure gradient at baseline (HR: 0.07; 95% CI: 0.01 to 0.70; p=0.02) were identified as independent predictors of 1-year adverse clinical outcomes, including all-cause death, myocardial infarction, stroke, and heart failure hospitalization. Conclusions: Appropriate P2Y12 inhibition by clopidogrel is a major determinant of adverse clinical events after TAVR. In sum, the present data challenges the need of DAPT as a standard therapy during TAVR. Funding Acknowledgement: Type of funding source: None